"When the Wild Roses Bloom": Indigenous Knowledge and Environmental Change in Northwestern North America. (15th November 2022) - Turner, Nancy J.; Reid, Andrea J.
Abstract: Indigenous Peoples in Northwestern North America have always worked with predictable cycles of day and night, tides, moon phases, seasons, and species growth and reproduction, including such phenological indicators as the blooming of flowers and the songs of birds. Negotiating variability has been constant in people's lives. Long‐term monitoring and detailed knowledge of other lifeforms and landscapes of people's home territories have assisted in responding and adapting to change. Aspects of cultural knowledge and practice that have helped Indigenous Peoples navigate nature's cycles at different scales of time and space include kin ties and social relationships, experiential learning, language, storytelling and timing of ceremonies such as "First Foods" celebrations. Working with ecological processes, Indigenous Peoples have been able to maintain optimal conditions for preferred species, reducing variability and uncertainty through taking care of productive habitats, leaving ecosystems intact, and allowing other species to change in their own cycles. Since the onset of colonization, however, Indigenous Peoples' lifeways have been changed drastically, culminating with the current impacts of global climate change and biodiversity loss. This paper, based on contributions of numerous Indigenous Knowledge holders from across Northwestern North America, outlines some of the key ways in which Indigenous Peoples have embraced predictability and change in their environments and lifeways, and addresses the particular threat of climate change: its recognition, ways of adapting to it, and, ultimately, how it might be reversed through developing more careful, respectful relationships with and responsibilities for the other‐than‐human world. Plain Language Summary: Indigenous Peoples of Northwestern North America have, for millennia, lived within seasonal cycles, using the life cycles of plants, birds, and other local species as indicators for harvesting. Their own calendars also mark the times of year when they can normally access and process the foods, materials, and medicines they rely upon and interact with. Indigenous Peoples have long held respectful, interdependent relationships with the plants and animals of their homelands, and have developed many different ways of tending and caring for these species, as well as creating adaptive practices, enabling them to respond to unanticipated shocks and events such as floods or unexpected loss of fish. The arrival of European colonizers caused many changes to Indigenous Peoples' lifeways, resulting in overall resource depletion and, most recently, drastic declines in biodiversity tied with global climate change, industrialization, and colonization. However, Indigenous Peoples' knowledge, practices, and strategies remain critically important, and are absolutely vital in identifying, alleviating, and reversing the impacts of these combined threats. Equally crucial are ethical ways of working together for the benefit of all. Key Points: Indigenous Knowledge has guided Peoples of Northwestern North America in optimizing their seasonal activities in synchrony with biological species The breadth and variety of Indigenous Knowledge prepared people for interannual variation, and helped them face the impacts with resilience Currently, with biodiversity loss and climate change threatening protective systems, Indigenous Knowledge is as critically important as ever